Teater Koma in a Changing Time 1977-2008 - Priatma, Rio; Suharto, Suharto (History Education, University of Jember, 2024)
This study discusses the dynamics of Teater Koma since its establishment, namely 1977 to 2008. The problems in this study are (1) How is the history of Teater Koma? (2) What were the dynamics of Teater Koma in 1977-2008 ?, and (3) How did Teater Koma influence the performing arts in Indonesia? The theory used is the performance function theory with a cultural sociology approach, and the method used was a historical method. Teater Koma is a theater group that was founded in Jakarta on March 1, 1977. Teater Koma was not originally born from an existing stage. The initial concept of its establishment, Teater Koma was not based on one particular color, but rather prioritized the search for the form and content of the theater which was more colorful. Teater Koma was initiated and founded by Nano Riantiarno together with 11 friends in Jakarta on March 1, 1977. From 1977 to 2008, Teater Koma has produced 112 performances, both performances and television dramas. Since its first performance, Teater Koma has experienced significant developments. Teater Koma has also experienced bans, ranging from suspicion, banning of performances, to the threat of bombs by the New Order government. The ban that was imposed did not make Teater Koma stop its creative process. Teater Koma as a theater group whose productivity is very diverse, has a very strong organizational management and human resources. Teater Koma considers itself to be born from society and repackaged for society. Entering the era of the 1980s, Teater Koma has developed by adding a new color to the development of performing arts in Indonesia, namely using mass media in different ways. This effort turned out to be accepted by the public and increasingly attracted by the audience.